Mengapa Indonesia Masih Harus Mengimpor Beras di Tengah Upaya Swambada - Ilham Ramadhan; Muhammad Muhammad; Try Rizwar; Muhammad Faiz Habibullah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Indonesia as an agricultural country has long been trying to achieve rice self-sufficiency to meet domestic food needs. However, although various policies and programs have been launched to support self-sufficiency, Indonesia still faces challenges that result in periodic rice imports. This study examines the main factors that cause dependence on rice imports, including limited agricultural land, climate change, inadequate irrigation infrastructure, and stagnant productivity at the farmer level. In addition, population growth and changes in consumption patterns have added pressure on domestic rice production. The analysis shows that successful self-sufficiency requires improvements in agricultural technology, infrastructure improvements, and policies that support sustainable farming. In conclusion, although Indonesia has great potential in rice production, the role of imports is still needed to balance fluctuations in domestic production and to ensure stable food security. The research method used is quantitative with data collection through access to Internet sites in the form of books, journals, and websites. According to data from the Central Statistics Agency (BPS), rice production in Indonesia has fluctuated due to several factors, such as the climate crisis, decreasing agricultural land and soil conditions, and access to irrigation. Rice production in the January-April 2024 period fell by 17.54% compared to the same period last year when it reached 22.55 million tons. Rice imports are a strategic step taken by the government to ensure the availability and stability of rice prices in Indonesia. Factors such as fluctuations in domestic production, high consumption needs, and efforts to maintain food reserves are the main reasons behind this decision. With a better understanding of the reasons and mechanisms of rice imports, it is hoped that the public can support this policy for the common good.